Pergulatan Sosioreligius di Tengah Arus Perubahan Ekonomi pada Masyarakat Kampung Inggris Pare Kediri - Ahmad Subakir (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
The establishment of educational institutes which mainly focus on English language course at Kampung Inggris (the Village of English) of Pare-Kediri plays pivotal role in the process of transformation of the local society especially in socio-religious and economic aspects they deal with. This article attempts to reveal socio-religious characteristic of the society at the Kampung Inggris along with their work ethos. The change of economic aspect has led to encounter of socio-religious aspect and the work ethos within the society as a result of the establishment of the English language courses coupled with the advent of outsiders who take the course. Employing socio-economic approach the study scrutinizes the dynamic of socio-religious aspect which grows as a consequence of the economic change. To get the necessary data and information, I use a panel of methods, which comprises interview, observation, and documentation. The discussion will focus on the socio-religious problems faced by the residents of the Kampung Inggris and their work ethos. The study finds that there has been a substantial change among the local society. The agrarian society at the Kampung Inggris has now transformed into capitalistic one. The transformation has subsequently affected their religious pattern from organic-religious to mechanic-religious.